2019
DOI: 10.2147/dddt.s208733
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differences in tolerability of pirfenidone between elderly and younger patients with idiopathic pulmonary fibrosis</p>

Abstract: Purpose Although pirfenidone (PFD) is a key drug for the treatment of idiopathic pulmonary fibrosis (IPF), differences in tolerability between elderly and young patients remain unclear. This study aimed to investigate age-related differences in adverse drug reactions to PFD and to evaluate whether patient age influences the safety and tolerability of PFD in clinical practice. Patients and method One hundred fifty-four patients with IPF were treated with PFD in our insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Disease progression itself might induce nausea. In elderly IPF patients, reduced gastrointestinal and metabolic function associated with aging, as well as irregular mealtimes, may be associated with nausea [ 29 ]. The management of nausea is important as it may deter patients from continuing pharmacotherapy, which could worsen the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression itself might induce nausea. In elderly IPF patients, reduced gastrointestinal and metabolic function associated with aging, as well as irregular mealtimes, may be associated with nausea [ 29 ]. The management of nausea is important as it may deter patients from continuing pharmacotherapy, which could worsen the disease.…”
Section: Discussionmentioning
confidence: 99%
“…We found that although the safety profile of nintedanib in patients aged ≥ 75 years was similar to that observed in younger patients, discontinuations of nintedanib due to adverse events occurred in a greater proportion of the older age group (26.4% vs 16.0%). Previous studies have also found that older patients are more likely to discontinue antifibrotic therapy [ 17 20 ]. The reasons for this are not known, but may reflect older patients being less able to tolerate the side-effects of antifibrotic therapy due to worse overall health, or to a difference in the perceived risk–benefit of treatment in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there were significant differences concerning the drug distribution between age groups: while pirfenidone was more often used in nonelderly, nintedanib was more common in elderly IPF which might be explained by different side effect profiles and tolerability of the individual drugs. Recently, it has been shown that over 1 year follow up patients with IPF ≥75 years are more likely to discontinue pirfenidone and have a higher incidence of gastrointestinal disorders ( 30 ). In our study, dose reduction and discontinuation of therapy occurred equally often in both age groups.…”
Section: Discussionmentioning
confidence: 99%